2012
DOI: 10.1186/1756-0500-5-683
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of paediatric corneal laceration injuries in the University of port Harcourt teaching hospital, Rivers state, Nigeria

Abstract: BackgroundCorneal lacerations mostly affect younger children, commonly males, who will constitute the majority of the workforce. Clinical outcomes are reviewed and compared so that measures to reduce their occurrence and improve outcome can be proffered.MethodsRecords of all children between the ages of 1-18 yrs, who presented with penetrating eye injuries at the eye clinic of the University of Port Harcourt teaching Hospital, Rivers state, Nigeria between January 2002 and December 2009 were included. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Missiles with stones, catapults, glass, knives, sport-related injuries, and fishing-related injuries are a few of the commonest causes of corneal lacerations that have been reported. 4 6 Corneal laceration caused by a river crab claw is an unusual case, and to the best of our knowledge it has not been reported in any literature thus far.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Missiles with stones, catapults, glass, knives, sport-related injuries, and fishing-related injuries are a few of the commonest causes of corneal lacerations that have been reported. 4 6 Corneal laceration caused by a river crab claw is an unusual case, and to the best of our knowledge it has not been reported in any literature thus far.…”
Section: Introductionmentioning
confidence: 82%
“… 2 It has been reported that 6.8%–14.7% of ocular traumatic injuries that present at emergency departments are corneal lacerations and perforations, 8 10 and these are the commonest finding in the pediatric age-group. 4 , 11 Omobolanle et al found that males have a higher incidence of corneal lacerations compared to females, with a ratio of approximately 3:1 and mean age of 8.7 years. 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations